The effect of maternal vitamin D deficiency during pregnancy on glycolipid metabolism of offspring rats and the improvement of vitamin D intervention after weaning - Chen, Zhaojun; Zhu, Yunxia; Wu, Ting; Qian, Xia; Hu, Ye; Hu, Wensheng (Frontiers in Nutrition, 2023)
Background Vitamin D deficiency during pregnancy is common, but whether maternal vitamin D status affects glycolipid metabolism of offspring remains unclear. Objective To evaluate the effect of maternal vitamin D deficiency during pregnancy on the glycolipid metabolism of offspring at different life-cycles (from birth to adulthood) and to explore the improvement of different dosages of vitamin D supplementation. Methods Sprague–Dawley rats were fed vitamin D-deprived (VDD group) or standard vitamin D diets (SC group) during pregnancy, and their diets were changed to standard vitamin D diets during lactation (the offspring were sorted into VDDoffspring and SCoffspring groups). After weaning, rats in the VDDoffspring group were randomly assigned to the VDDoffspring, VDDoffspring-S3300 and VDDoffspring-S10000 groups with diets containing standard, medium and high dosages of vitamin D for 12 wk. Serum was collected for biochemical analyses at postnatal Day 21, postnatal Day 56 and postnatal Day 84. Oral glucose tolerance test (OGTT) was performed at postnatal Day 70. Results Compared to SCoffspring, rats in the VDDoffspring group had significantly lower birth weight with faster weight gain and higher levels of lipid metabolism in early life. After near adulthood, the differences in weight and lipid metabolism between the two groups disappeared. OGTT showed significantly higher blood glucose levels in the VDDoffspring group at 30 min, 60 min, and 90 min. The continuation of vitamin D supplementation at medium and high dosages after weaning did not cause any obvious changes in weight or glycolipid metabolism (except for postprandial hyperglycemia). OGTT demonstrated that the glucose levels in the VDDoffspring-S3300 group were lowest at all the time points and that those in the VDDoffspring-S10000 group were the highest at 30 min, 60 min, and 90 min among the three groups. Conclusion The adverse effects of vitamin D deficiency during pregnancy on glycolipid metabolism in offspring vary in different stages. Over a long time period, adequate vitamin D supplementation is beneficial to glycolipid metabolism for the offspring of subjects with vitamin D deficiency during pregnancy; however, further improvement is required.